2020
DOI: 10.3390/ijerph17072582
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Internet Addiction and Gaming Disorders in Southeast Asia: A Meta-Analysis

Abstract: This meta-analytic review aimed to examine the pooled prevalence rates of Internet addiction and gaming disorders in Southeast Asia. Several databases including PubMed, MEDLINE, PsycINFO, Web of Science, Embase, and Cochrane Central were searched and a total of 24 studies were included in this study. The selection of studies was conducted in accordance to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Two meta-analyses were conducted to examine data on Internet addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 42 publications
7
72
2
7
Order By: Relevance
“…In a recent meta analysis the rate of internet addiction was 7.2% in the general population, which is far lower than it would be expected by the IA rate of adolescents which can be as high as 20% (13,14). In out study the rate of IA was 5.2%, which is comparable to the above mentioned ndings.…”
Section: Discussionsupporting
confidence: 53%
“…In a recent meta analysis the rate of internet addiction was 7.2% in the general population, which is far lower than it would be expected by the IA rate of adolescents which can be as high as 20% (13,14). In out study the rate of IA was 5.2%, which is comparable to the above mentioned ndings.…”
Section: Discussionsupporting
confidence: 53%
“…It can be speculated that young adults and college students tend to have more autonomy and opportunities to use smart devices than younger students do. Therefore, due to their technological proficiency and lack of external supervision, they may be more prone to suffer from gaming disorders ( 14 ). More research is needed to verify these results.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the differences in measurement tools and cultural backgrounds, different prevalence rates of IGD were reported among young people. For example, prevalence in Europe was between 1.2 and 1.6% (11,12), while in Asia it ranged from 1.6 to 18.4% (13)(14)(15). Some studies reported that the rates of possible IGD among adolescents in China ranged between 2.0 (15) and 17.0% (16).…”
Section: Introductionmentioning
confidence: 99%
“…Although this technological revolution has improved many aspects of our lives and it is now an essential part of the everyday routine, including work, private life and social functioning, many studies reported the misuse of internet (problematic internet use, internet addiction; IA) as summarized in a recent meta-analysis including 113 epidemiologic studies covering 693,306 subjects showed that the pooled prevalence of internet addiction was 7.02% (95% CI, 6.09–8.08%) in the population aged 7–60 years [ 1 ]. Age (adolescent samples), lower cut-off scores (and type of questionnaire), sample size (more common is smaller samples), and country of origin (more frequent in Asian studies) were significant predictors of higher prevalence [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%